Marketing Activities of the Municipality of Majur - Bugarin, Dario; Markešić, Tomislav; Oblaković, Dorotea; Stručić, Martin (Strategije za održivi i ruralni razvoj gradova Siska, Petrinje i Hrvatske Kostajnice i općina Majur i Topusko, 2025)
The municipality of Majur is located in Sisak-Moslavina County and is known for its unique Woonko Wool Centre, the only one of its kind in Croatia. The centre has an educational character and visitors can see wool products, make their own wool souvenirs and have an unforgettable experience of virtual wool shearing. The aim of the research is to identify the problems faced by the Municipality of Majur and the Woonko Wool Centre and to propose solutions that will improve the marketing activities of the Municipality of Majur and the Woonko Wool Centre. Therefore, this paper is based on a description of the destination, the exploration of a marketing strategy, a proposal for promotion via social networks, the creation of an innovative and attractive emblem and the improvement of the visibility of signposts. The purpose of the paper is for the students' research proposals to serve as a tool for developing the potential of the community of Majur and the Woonko Wool Centre through the proposed marketing activities.